2022
DOI: 10.1038/s41598-022-07544-2
|View full text |Cite
|
Sign up to set email alerts
|

Standardized evaluation of the quality and persuasiveness of mobile health applications for diabetes management

Abstract: This study evaluates diabetes self-management mobile health applications available from European app stores with respect to quality, concordance with recommended self-management tasks and implementation of persuasive system design principles. The European Play Store and Apple App Store were systematically searched and relevant apps were tested. Two raters independently assessed app quality using the Mobile Application Rating Scale and conducted a content analysis of provided persuasive system design principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
8
1
Order By: Relevance
“…Also, in this study, the user score was correlated with the overall score of MARS as well as the subjective quality score of the MHA, which was in contrast to previous studies that reported no correlation between the MARS score and the user score [24,26,34,35]. Given that users often rely on user ratings when choosing an app to download [22], this is an encouraging nding that there is a correlation between user ratings and MARS ratings for Persian maternity care MHAs.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Also, in this study, the user score was correlated with the overall score of MARS as well as the subjective quality score of the MHA, which was in contrast to previous studies that reported no correlation between the MARS score and the user score [24,26,34,35]. Given that users often rely on user ratings when choosing an app to download [22], this is an encouraging nding that there is a correlation between user ratings and MARS ratings for Persian maternity care MHAs.…”
Section: Discussioncontrasting
confidence: 86%
“…We examined the features and quality of the selected MHAs, then obtained the features of MHAs from Frid et al study [18] and other available documents [19][20][21][22]. We categorized them into general features (15 features) and speci c features (14 features) of maternity care MHA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have described the needs and preferences of patients with T2DM and factors that could encourage engagement with mHealth apps to support selfmanagement [17,18,23]. For example, people with T2DM would prefer an app to address the practical aspects of diabetes self-management and to reduce the cognitive burden of selfmanagement [24]. However, very few studies have been conducted among patients with T2DM in the context of Asian healthcare and cultural settings.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are using mobile health applications more frequently as a result of the global proliferation of mobile device technology. 9 More than 2.5 billion individuals will own smartphones by the year 2019, and by 2017, more than 50% of them will have mobile health applications installed. 10 More than 60% of people in the USA use digital devices and mobile health apps to manage their health.…”
Section: Introductionmentioning
confidence: 99%